TAPERA: Melindungi Hak Atas Tempat Tinggal Atau Mengancam Kehidupan Yang Layak - Samuella, Elizabeth Jeneva; Susanti, Ida (Jurnal Hukum & Pembangunan, 2025)
This study examines the People's Housing Savings (TAPERA) policy in the context of protecting the right to adequate housing and its impact on the decent living conditions of workers. Under TAPERA regulations, all workers are required to set aside a portion of their salary, including those who already own a home. While this policy aims to improve access to adequate housing, it raises questions about its impact on purchasing power and the fulfillment of other basic needs. The study employs an interdisciplinary approach using socio-legal methods to evaluate whether the mandatory TAPERA contributions can be considered a violation of the right to a decent life. Findings indicate that this policy potentially reduces the budget allocation for essential needs such as food, education, and healthcare, thereby threatening the welfare of workers. Proposed solutions include exempting workers who already own homes from the contribution requirement and enhancing transparency in TAPERA fund management. The study recommends a more flexible and fair approach to ensure that TAPERA's goals are achieved without compromising the overall well-being of the community.